IMF Staff Papers, Volume 55, No. 3. (IMF Staff Papers; IMF Staff Papers ;, 2008)
This special issue on exchange rates is drawn from the Eighth Jacques Polak Annual Research Conference held at the International Monetary Fund in Washington in November 2007. The Mundell-Fleming Lecture by Stanley Fischer focuses on exchange rate systems, surveillance, and advice. Jeffrey Frankel and Shang-Jin Wei examine the techniques for estimating de facto exchange rate regimes, while J. Lawrence Broz, Jeffry Frieden, and Stephen Weymouth review survey data to discern exchange rate policy attitudes. In a paper entitled "Fear of Declaring", Adolfo Barajas, Lennart Erickson, and Roberto Steiner try to determine the extent to which markets care about what countries say regarding their exchange rate policies.